Montacute House - Phelips, Sir Edward
The house is in the tradional H arrangement with two parallel wings connected by a narrow section. The pasage at the back of this section was formed of the porch and part of the walls form an earlier house at Clifton Maybank and is definitley Late Tudor. The carvings, however, are of Italian charater, and the parapets have cusped panels. The pinnacles, in the Tudor spirit, have a spiral twist. The windows, with a symmetrical arrangement, have, at the center, the bay which was moved from the end where it was traditionally found. For all the tradtional Tudor arrangments, the windows are set deep in the classic manner. Along the top floor in the spaces between the windows are eight statues with a ninth in the central gable. These represent the Nine Worthies. Dutch gables were seen in illustrated books of the time, especially those of Vredman de Vries which were published in Holland in 1565 and 1568. These gables are, prehaps, an indication of a last fling of architectural invention before the strict rule of Renaissance Italy was applied in England, and they were to give a few more years extension to this transitional period between Gothic and classical architecture.